Features abortion in adolescent Dos de Mayo Hospital. - Aparicio, Jorge (2015)
OBJECTIVE: To determine the characteristics of adolescents attended for abortion at Dos de Mayo Hospital. DESIGN: Revision 71 cases of patients less than 20 years old with diagnosis of abortion. Two cases were excluded because of missing anatomopathologic report and/or lack of congruency between pathological and clinical diagnosis. Data were obtained in a special chart. RESULTS: Age was between 16 and 19 years in 92,7%, not married 55,1%. Almost no patient had prenatal control (97,1%). Most frequent preliminary diagnosis was incomplete abortion in 86,9016. Contraceptive method was used only by 40,6%, and 26,08% used natural methods. Previous abortion ocurred in 10,1%. Most serius complication was pelviperitonitis and hysterectomy was needed. CONCLUSION: Abortion in adolescents occurs in late adolescence and in women with low sociocultural status and no prenatal control.